Design, synthesis, in vitro and in vivo evaluation, and structure-activity relationship (SAR) discussion of novel dipeptidyl boronic acid proteasome inhibitors as orally available anti-cancer agents for the treatment of multiple myeloma and mechanism studies. Issue 14 (7th August 2018) - Lei, Meng; Feng, Huayun; Bai, Enhe; Zhou, Hui; Wang, Jia; Shi, Jingmiao; Wang, Xueyuan; Hu, Shihe; Liu, Zhaogang; Zhu, Yongqiang
Graphical abstract: Highlights: Aliphatic groups at R 1 position were synthesized to fully understand the SAR. 6a inhibited the CT-L activity and the MM cells RPMI8226, U266B and ARH77. 6a showed almost the same bioavailability as MLN2238 . 6a inhibited cell cycle progression at the G2M stage. 6a significantly inhibited tumor growth in a human ARH77 MM xenograft mouse model. Abstract: A series of novel dipeptidyl boronic acid inhibitors of 20S proteasome were designed and synthesized. Aliphatic groups at R 1 position were designed for the first time to fully understand the SAR (structure–activity relationship). Among the screened compounds, novel inhibitor 5c inhibited the CT-L (chymotrypsin-like) activity with IC50 of 8.21 nM and the MM (multiple myeloma) cells RPMI8226, U266B and ARH77 proliferations with the IC50 of 8.99, 6.75 and 9.10 nM, respectively, which showed similar in vitro activities compared with the compound MLN2238 (biologically active form of marketed MLN9708 ). To investigate the oral availability, compound 5c was esterified to its prodrug 6a with the enzymatic IC50 of 6.74 nM and RPMI8226, U266B and ARH77 cell proliferations IC50 of 2.59, 4.32 and 3.68 nM, respectively. Furthermore, prodrug 6a exhibited good pharmacokinetic properties with oral bioavailability of 24.9%, similar with MLN9708 (27.8%). Moreover, compound 6a showed good microsomal stabilities and displayed stronger in vivo anticancer efficacy than MLN9708 in the human ARH77 xenograft mouse model. Finally, cell cycle results showed that compound 6a had a significant inhibitory effect on CT-L and inhibited cell cycle progression at the G2M stage.